Early enteral nutrition with exclusive donor milk instead of formula milk affects the time of full enteral feeding for very low birth weight infants - Wang, Min; Gong, Xiaohui; Yu, Lianhu; Song, Feifei; Li, Dan; Fan, Qiaoling; Zhang, Ting; Yan, Xueming (Frontiers in Nutrition, 2024)
This study investigated the effects of exclusive donor milk or formula in the first 7 days after birth, on the time to full enteral feeding, growth, and morbidity of adverse events related to premature infants. This was a retrospective study carried out from July 2014 to December 2019 at the Department of Neonatology of Shanghai Children’s Hospital. All infants with a birth weight < 1,500 g and a gestational age ≤ 32 who received exclusive donor milk or formula in the first 7 days after birth were included in this study. The time to full enteral feeding (defined as 150 mL/kg) in the donor milk group was significantly shorter than in the formula group (18 vs. 22 days, p = 0.01). Donated breast milk was also associated with a lower incidence of NEC (4.4 vs. 7%, p < 0.01), ROP (3.8 vs. 13.2%, p < 0.01), and culture-confirmed sepsis (11 vs. 22.6%, p < 0.01). Using donated breast milk instead of current formula milk for early enteral nutrition can shorten the time to full enteral feeding and reduce the incidence of NEC, ROP, and sepsis.